Menjadi Eksportir Fashion Muda Indonesia Melalui Program Studi Independen Di Lacorre - Aura Alfnavisa Az-Zahra; Supriyono Supriyono (CV. Aksara Global Akademia, 2024)
Global competitiveness views exports as one of the important aspects in the economic development of a country. Through the independent study program at LaCorre, it aims to create thousands of young exporters to help advance the Indonesian economy. LaCorre provides a forum for students who want to learn, develop, and export products, especially in the fashion sector that is globally competitive by leveraging digital technology. In the independent study program at LaCorre, students are required to engage in a series of learning activities, starting from the preparation of export materials, export lectures, mentoring, Export Roadshow (JJE), and practical work to writing export final works. This aims to equip students with the skills and knowledge needed to be a successful young exporter. The practice of developing a digital-oriented export business plan is the main activity of the independent study program at LaCorre. In this practice, the author collaborated with a team to develop one of the batik products from Indonesian SMEs in order to help facilitate exports and expand the market share of batik products. Overall, the independent study program for one semester went effectively because it had achieved the learning objectives on time.